TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP SEWA MENYEWA TANAH SECARA BERUNTUN DI DESA TAMAN SARI KECAMATAN GUNUNG SARI KABUPATEN LOMBOK BARAT - Muhammad Firman Hidayat; Muhammad Nor (Universitas Islam Negeri Mataram, 2024)
This study aims to explain the practice of consecutive land leases in Taman Sari Village, Central Lombok Regency in the perspective of Islamic economic law. The research method used in this study is field research with a qualitative approach. While the research findings, In practice, consecutive land leases carried out by land owners and tenants are carried out directly with an unwritten agreement pattern, but only verbally. In the event that an agreement has been made and mutually agreed upon, the tenant has the right to use the land according to his wishes with a period of time that has been mutually agreed upon. While the principle of ijarah (rent) in Islam. When the lease period ends, the land that has been used will automatically return to the landowner without redemption or payment of the rental fee that has been issued by the tenant being returned. The tenant is also not allowed to re-rent goods that are not his own to other people.